Stable phases of the Cs2CuCl4-xBrx mixed systems - Krüger, N; Belz, S; Schossau, F; Haghighirad, A; Cong, P; Wolf, B; Gottlieb-Schoenmeyer, S; Ritter, F; Assmus, W (2010)
Starting from Cs2CuCl4 and Cs2CuBr 4, we focus on the growth of the Cs2CuCl 4-xBrx mixed crystals from aqueous solution and the investigation of the occurring structural variations. The well-known orthorhombic structure (space group Pnma) of the end members of this system is interrupted within the intermediate composition range from Cs 2CuCl3Br1 to Cs2CuCl 2Br2, if the growth takes place at room temperature. Within this range, a new tetragonal phase is found (space group I4/mmm). However, in case the growth temperature is increased to 50 °C, the existence of the orthorhombic structure can be extended over the whole Cs 2CuCl4-xBrx mixed system. A detailed analysis of the composition dependence of the lattice parameters is used to draw conclusions about the incorporation of Cl and Br ions at different sites, which is important for the magnetic interactions between the Cu ions. © 2010 American Chemical Society.